Insomnia and posttraumatic stress symptoms: Evidence of shared etiology. (April 2020) - Cox, Rebecca C.; Taylor, Steven; Strachan, Eric; Olatunji, Bunmi O.
Highlights: Examined the genetic contributions to the relation between insomnia and PTSD symptoms. Results indicated a significant association between insomnia and trauma intrusions. Results indicated a significant association insomnia and avoidance. 36–44% of phenotypic variance was accounted for by genetic contributions. Abstract: Posttraumatic stress disorder (PTSD) and insomnia are comorbid clinical conditions that are thought to result from genetic and environmental effects. Though studies have established the heritability of these disorders independently, no study to date has examined the genetic contributions to the relation between insomnia and PTSD symptoms (PTSS). The present study assessed this gap in the literature using a behavioral genetics approach to symptom dimensions. The sample consisted of 242 twin pairs who endorsed lifetime trauma exposure. Insomnia symptoms were assessed with the Women's Health Initiative Survey, and intrusion and avoidance PTSS were assessed with the Impact of Events Scale. Structural equation modeling was then employed to test the relative contributions of genetic, shared environmental, and nonshared environmental components to the relations between insomnia symptoms and intrusions and avoidance. Results indicated a significant association between insomnia symptoms and intrusions ( r  = 0.33, p  < 0.01) and insomnia symptoms and avoidance ( r  = 0.20, p  < 0.01), and 36–44% of phenotypic variance was accounted for by genetic contributions. These findings highlight a significant role for genetic factors in the mechanisms underlying the comorbidity between insomnia and PTSS. The implications for current etiological models of PTSD and insomnia are discussed.